Use of Artificial Intelligence in the Judiciary of the People’s Republic of China - Borkowski, Grzegorz (Wykorzystanie sztucznej inteligencji w sądownictwie w Chińskiej Republice Ludowej, 2024)
Aim: The article analyses the application of artificial intelligence (AI) in the judiciary of the People’s Republic of China, focusing on “smart courts” and their functionalities, such as data analysis, speech recognition, and automated judgment generation. It also discusses challenges, including the “black box” problem and accountability for errors. Methodology: The analysis includes a case study of the FITS (Full-Process Intelligent Trial System) and other examples of AI implementation in the Chinese judiciary, such as ODR platforms. The study also considers the historical context of AI technology development in law, providing a broader perspective on the Chinese solutions. Results: AI enhances judicial efficiency by streamlining processes and improving citizens’ access to justice. However, excessive reliance on AI poses risks, such as reducing the role of judges, lack of algorithmic transparency, and data protection issues. Implications and recommendations: Implementing AI in the Polish judiciary requires caution, balancing automation and human oversight, and ensuring data protection and technological transparency. Originality/value: The article offers a unique analysis of the Chinese judicial system and its technologies, providing valuable insights for countries planning to digitalise their judicial systems.
Business Informatics = Informatyka Ekonomiczna, 2024, Nr 1-2 (67-68), s. 127-139
Keywords: competent courts; AI; judiciary; China; digitalisation; inteligentne sądy; sądownictwo; Chiny; cyfryzacja